2018
DOI: 10.1111/ejn.14071
|View full text |Cite
|
Sign up to set email alerts
|

Auditory motion does not modulate spiking activity in the middle temporal and medial superior temporal visual areas

Abstract: The integration of multiple sensory modalities is a key aspect of brain function, allowing animals to take advantage of concurrent sources of information to make more accurate perceptual judgments. For many years, multisensory integration in the cerebral cortex was deemed to occur only in high-level "polysensory" association areas. However, more recent studies have suggested that cross-modal stimulation can also influence neural activity in areas traditionally considered to be unimodal. In particular, several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Considering the relatively slow conduction of the visual pathway, and the fact that visual response latencies increase further when stimuli have low visibility (Bourne et al 2002 ; Lui et al 2012 ), a reciprocal projection from V1 to auditory areas would not provide a similar processing advantage. A sparse projection from caudal auditory cortex to area MT (Palmer and Rosa 2006a ) has been hypothesised to facilitate processing of visual motion, but recent single-neuron recording studies have not been able to confirm the existence of such an effect (Chaplin et al 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the relatively slow conduction of the visual pathway, and the fact that visual response latencies increase further when stimuli have low visibility (Bourne et al 2002 ; Lui et al 2012 ), a reciprocal projection from V1 to auditory areas would not provide a similar processing advantage. A sparse projection from caudal auditory cortex to area MT (Palmer and Rosa 2006a ) has been hypothesised to facilitate processing of visual motion, but recent single-neuron recording studies have not been able to confirm the existence of such an effect (Chaplin et al 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…The neural representation of auditory motion does not necessarily have to be located in purely auditory regions. Direct reciprocal connections between MT/MST and the auditory cortex have been identified in primates (Palmer and Rosa, 2006 ), and two recent electrophysiological studies (Chaplin et al, 2018 ; Kafaligonul et al, 2018 ) have reported evoked potentials in areas MT/MST in response to stationary auditory clicks. Two human imaging studies have reported that the hMT+ complex responds to auditory motion (Poirier et al, 2005 ; Strnad et al, 2013 ), but it has also been argued that observed auditory responses in hMT+ could be explained by localization errors (Jiang et al, 2014 ), and no study has found any evidence for spiking activity in response to auditory stimuli (moving or stationary) in the monkey MT complex.…”
Section: Auditory Motion Processing Areasmentioning
confidence: 99%
“…A number of imaging studies have also found that audiovisual stimulation produces distinct activation (compared to visual only stimulation) in hMT+ (Alink et al, 2008 ; Lewis and Noppeney, 2010 ; Strnad et al, 2013 ; von Saldern and Noppeney, 2013 ), suggesting that auditory stimuli can modulate visually evoked responses (although this is not always the case, e.g., Wuerger et al, 2012 ). These regions receive sparse inputs from auditory cortex (Palmer and Rosa, 2006 ), and show evoked potentials in response to auditory stimuli (Chaplin et al, 2018 ; Kafaligonul et al, 2018 ). Additionally, auditory motion has been shown to affect various aspects of visual perception, such as improving visual motion detection (Kim et al, 2012 ), improve learning in visual motion tasks (Seitz et al, 2006 ), and induce visual illusions (Sekuler et al, 1997 ; Meyer and Wuerger, 2001 ; Kitagawa and Ichihara, 2002 ; Beer and Röder, 2004 ; Soto-Faraco et al, 2005 ; Freeman and Driver, 2008 ; Alink et al, 2012a ; Kafaligonul and Stoner, 2012 ; Kafaligonul and Oluk, 2015 ).…”
Section: Audiovisual Motion Integration In the Primate Cerebral Cortementioning
confidence: 99%
See 2 more Smart Citations